Beyond species identification: integrative methodologies for solving complex wildlife forensic cases - Kahila Bar-Gal, Gila (Frontiers in Ecology and Evolution, 2025)
IntroductionEnvironmental crimes, such as illegal hunting, trade, smuggling, poisoning, and harvesting of protected wildlife, rank among the world’s top five illicit activities, contributing significantly to biodiversity loss. Wildlife forensic cases often involve multiple domestic and wild species and require a multidisciplinary approach for effective resolution. The enforcement of wildlife protection laws increasingly depends on molecular genetic methods.GoalsIn this study, I present three complex wildlife forensic cases involving the poisoning of the Eurasian griffon vulture (Gyps fulvus), critically endangered (CR) in Israel, and the poaching of wildlife, including the Nubian ibex (Capra nubiana) and gazelles (Gazella spp.), particularly the endangered mountain gazelle (Gazella gazella).Results and DiscussionThese cases underscore the importance of integrating methodologies, beginning with species identification, population assignment, and individual sample matching using public and local genetic databases to ensure comprehensive analysis. The local genetic databases play a crucial role in providing essential species and population validation. The involvement of both wild and domestic species in each case necessitates an efficient, accurate, rapid, and cost-effective protocol to differentiate wild from domestic species among exhibits seized at crime scenes and to confirm the identity of wild species beyond any doubt.